Changes and continuities in families with migrant parents who have returned to Antioquia and the Colombian coffeegrowing region - Jair Eduardo Restrepo Pineda (Migraciones, 2017)
This article carries out an approach to the families immersed in a migratory process of international return of their fathers and mothers, allowing to make visible the modification and reconfiguration of their dynamics and how these affect the relations, cohabitation and functioning of family life. Aspects such as authority and decision-making, gender roles and economic supply are the ones that demonstrate greater changes for every member of the family unit. As regards the continuities, it is highlighted the fact that the carer role is still being inherently bound to the women. The return is a dynamic process in which communication, care and economic supply prepare the migrants’ way towards their reincorporation into family life.